1998
DOI: 10.1002/(sici)1521-3951(199806)207:2<387::aid-pssb387>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Charge Localization around Disclinations in Monolayer Graphite

Abstract: Using a continuum model, we obtain qualitative results that imply charge localization around negative curvature disclinations (i.e. rings with more than six carbon atoms) in a graphite sheet. Conversely, it is found that positive curvature disclinations repel charge, independent of its sign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…In this approach the defects are represented by metrics that are solutions of Einstein-Cartan equations in three space dimensions. An application of this model to graphite has appeared in [8], where localization of charge near heptagonal rings has been verified. In this geometrical background we analyze the global properties of the massless Dirac equation that describes the electronic spectrum of graphite at the Fermi level [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this approach the defects are represented by metrics that are solutions of Einstein-Cartan equations in three space dimensions. An application of this model to graphite has appeared in [8], where localization of charge near heptagonal rings has been verified. In this geometrical background we analyze the global properties of the massless Dirac equation that describes the electronic spectrum of graphite at the Fermi level [9].…”
Section: Introductionmentioning
confidence: 99%
“…The Schrödinger equation in the presence of dislocations was considered in for different problems. Problems related to the wave or Laplace equations were considered in [47][48][49][50][51][52][53][54]. The influence of the nontrivial metric related to the presence of defects was investigated in electrodynamics [55] and hydrodynamics [56].…”
Section: Introductionmentioning
confidence: 99%
“…A similar result has been obtained in [27] with numerical simulations. It is to note that a somehow contradictory result was obtained in [28] where they studied the electrostatics of a graphene plane with defects. They found that disclinations corresponding to rings with more (less) than six carbon atoms function as attractors (repellent) to point charges.…”
mentioning
confidence: 99%